Proceedings - National Conference [on] Women and Men in Changing Societies (2002 : Bangi); Bahiyah Dato' Haji Abdul Hamid; Southeast Asian Association for Gender Studies, Malaysia Branch; Universiti Kebangsaan Malaysia. Fakulti Sains Sosial dan Kemanusiaan. Pusat Pengajian Sosial, Pembangunan dan Persekitaran ([Bangi] : Southeast Asian Association for Gender Studies, Malaysia Branch, 2002)
Contained paper work on re-examination of cultural constructs of gender, gender relations and gender issues in relation to development, globalisation and modernization in the Southeast Asian region is indeed essential and timely
Microsoft Word format
CD-ROM is corrupted
Keywords: Socialism and culture -- Congresses; Social change -- Sex differences -- Congresses; Culture -- Sex differences -- Congresses; Sex discrimination in economics -- Congresses